Application of micellar liquid chromatography for the determination of antitumoral and antiretroviral drugs in plasma. (July 2014) - Peris-Vicente, Juan; Casas-Breva, Inmaculada; Roca-Genovés, Pasqual; Esteve-Romero, Josep
In micellar liquid chromatography, the mobile phase is made of a surfactant and, eventually, an alcohol. This article describes several methods to measure the concentration of antitumoral and antiretroviral drugs in plasma, utilizing micellar liquid chromatography. Samples can be injected after dilution with a micellar solution and filtration, because proteins and other endogenous compounds are solubilized in micellar medium. We will discuss the following optimized parameters: dilution ratio, type of column, detection conditions and mobile phase composition. This article will also cover the validation performed following the International Conference on Harmonization guidelines and the results reported in the literature, indicating that the methods are useful for the routine analysis of plasma samples for clinical purposes.